JEREMIAD FRAMES IN REAGAN’S INAUGURAL ADDRESSES - Mister Gidion Maru (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
This research attempts to examine the existence of frames from jeremiad tradition as part of American values in an American president’s inaugural address. The function and context of the frames are also investigated. These aims are achieved by applying Goffman’s Frame Analysis on the text of Reagan’s inaugural addresses. This inaugural addresses is chosen because Reagan’s presidency is regarded to set the tone for the following presidencies; his presidency faced crises which other presidents following him have also faced; and he is viewed as one of the best orators among American presidents. The results show that Ronald Reagan’s inaugural addresses use the jeremiad frames which are categorized into three forms, namely, the lamentation of the present, the evocation of the past and the calling for renewal. By using these frames in combination with the context of the inaugural address, Reagan presents American perspective and hopes for their situation and future.